An optical investigation of substitution rates on natural gas/diesel dual-fuel combustion in a diesel engine. (1st March 2020) - Lee, Chia-fon; Pang, Yuxin; Wu, Han; Nithyanandan, Karthik; Liu, Fushui
Highlights: Flame development process of CNG/diesel dual-fuel was studied in a light-duty engine. With CNG increasing, ignition delay period prolongs and the premixed flame enhances. Flame cores form at multiple zones near the wall and then propagate towards center. Increasing CNG substitution ratio decreases high-temperature and KL factor regions. Abstract: Compressed natural gas/Diesel dual-fuel combustion mode, the partial replacement of diesel fuel with cleaner fuel, is one of the most important strategies to achieve clean efficient combustion. Thus, the current work investigated the effect of various natural gas substitution ratios on the combustion and soot emission characteristics experimentally in an optical diesel engine. Experiments were performed at different compressed natural gas (CNG) substitution rates of 30%, 50%, 70%, 85% (based on energy) over a wide range of equivalence ratios of the premixed charge. In-cylinder flame images were captured by a high-speed camera and further processed to obtain flame characteristics as well as soot distributions. The results show that the effect of natural gas is reflected mainly in the premixed flame area and a change of the ignition delay period. As the substitution ratio increasing, the pressure and the heat release rate decrease, while the ignition delay period prolongs and the premixed flame distribution is more extensive. Besides, high-temperature regions and the soot volume fraction decrease, especially at higher substitution ratios conditions. Through controlling the natural gas substitution ratios, an efficient and clean combustion mode for dual-fuel engines can be found. In general, higher natural gas substitution rate leads to cleaner combustion trends and more desirable flame characteristics.